FAKTOR-FAKTOR YANG MEMPENGARUHI CAPITAL STRUCTURE PADA PERUSAHAAN MANUFAKTUR - Natasha Laviola; Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this study is to determine the effect of profitability, firm size, asset tangibility, non-debt tax shield, and business risk on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The sample selection technique used in this study was purposive sampling with a total sample size of 198 samples. Data processing from this sample is assisted by the Statistical Package for Social Science (SPSS) software version 23. The results obtained from this study indicate that profitability has a significant negative effect on capital structure, while firm size, asset tangibility, non-debt tax shield, and business risk do not have a significant effect on the capital structure.